Demonstration of Laser-Fabricated DLSPPW at Telecom Wavelength - Andreas Seidel (IEEE Photonics Journal, 2010)
We investigate dielectric-loaded surface plasmon-polariton waveguides (DLSPPWs) fabricated by two-photon polymerization direct laser writing and nanoimprinting at the telecom wavelength of 1550 nm. We examine several types of structures such as lines and bends as individual plasmonic components. Racetrack resonators are presented as a potential application of this technology. These plasmonic components can be investigated at 1550-nm wavelength by leakage radiation microscopy using an InGaAs camera. The experimentally observed behavior of these components in a leakage radiation microscope matches the theoretical expectations. The results demonstrate the practical feasibility of laser-fabricated DLSPPW components at telecom wavelength.